Assessment of On-Farm Saved Chickpea (Cicer arietinum L.)Seed Quality in Central Ethiopia - Sori, Abebe; Bishaw, Zewdie; Fikre, Asnake; Dejene, Mashilla; Kaske, Karta (Wiley Open Access, 2025)
Limited information exists on the impact of current seed storage methods on seed quality in Central Ethiopia. The study aimed to assess the extent of the decline in seed quality of on-farm stored chickpeas. Two hundred two farmers were identified using a multistage and purposive technique, and seed samples were collected from five districts. Two rounds of on-farm seed samples were collected at early storage in March and at planting time in September 2022. Seed quality tests, including physical purity, physiological quality, and seed health were conducted using standard laboratory techniques for the seed samples. In Round 1, the results showed that mean physical purity, seed moisture (SM, %), and seed germination (SG, %) were 94.9%, 10.7%, and 83.8%, respectively. Moreover, about 95.5% and 81.8% of the seed samples satisfied the certified seed class D standards for SM and SG, respectively. However, for Round 2, the samples met the certified seed class D standard for SM and standard SG dropped to 36.9% and 63.1%, respectively. In Round 1, seed infection varied between 12% and 80%, whereas in Round 2, seed infection varied between 25% and 100%. During both rounds of seed sampling, no seed sample fulfilled the standard for certified seed class D specified for chickpea seed infection (%). Overall, seed quality was considerably lower during planting time compared to early storage. The study showed challenges in maintaining seed quality using current seed production, seed storage, and management practices indicating a need to improve seed production, processing, and handling practices to enhance farm-level chickpea seed quality and productivity.